Molecular & Diagnostic Imaging in Prostate Cancer Clinical Applications and Treatment Strategies (Advances in Experimental Medicine and Biology,, 2018)
The second of two companion books which address the biology and clinical aspects of prostate cancer. This volume, Prostate Cancer: Molecular & Diagnostic Imaging and Treatment Stategies, discusses both classic and the most recent imaging approaches for detection, early diagnosis and treatment of prostate cancer. The companion title, Cell & Molecular Biology of Prostate Cancer, covers classic and modern cell and molecular biology as well as genetics, epigenetics, mitochondrial dysfunctions and apoptosis, cancer stem cells, angiogenesis, progression to metastasis, and treatment strategies including clinical trials related to prostate cancer. Taken together, these volumes form one comprehensive and invaluable contribution to the literature. .